Ecotourism Potentials of Plateau State, Nigeria: A Monitoring Survey (2011)
Endowment with natural attractive features is one of the important indicators of a successful development of ecotourism, as simulation of ecotourism potentials can signiﬁcantly affect patronage by making experience unnatural. This survey was conducted using oral interviews, group discussions, a reconnaissance survey and information obtained from administrative records of ecotourism institutions. The results obtained were analysed using descriptive statistics and presented in the form of tables and a graph. The study revealed that Plateau State is endowed with potential packaged in many tourism centres, such as Pandam Wildlife Park, Jos Wildlife Park, Jos National Museum and Zoo, Wase Wildlife Park, Assop Falls, Naraguta Tourist Village, Rayﬁeld Resort, Pai River Game Reserve and Amurun Bird Sanctuary, and these are stocked with different tourism products. Some of the products include viewing game, wilderness tourism, bird watching, ﬁshing, and recreational and cultural tourism. On an annual basis, the Jos National Museum and Zoo recorded the highest number of tourists, about 300,000 in 2003, 2004 and 2007. A cumulative 424,252 tourists visited the surveyed ecotourism destinations of Plateau State in 2004, while 112,648 visited in 1998. December had a relatively high number of tourists throughout the period of the study. There was a progressive increase in the cumulative number of ecotourists from 1998 to 2004. These tourism potentials, if properly and fully harnessed, could make Plateau State and the various tourism centres ﬁnancially independent.